Associations among human papillomavirus, inflammation, and fatigue in patients with head and neck cancer. Issue 15 (9th May 2018) - Xiao, Canhua; Beitler, Jonathan J.; Higgins, Kristin A.; Glazer, Toby; Huynh, Linh Kha; Paul, Sudeshna; Felger, Jennifer C.; Wommack, Evanthia C.; Saba, Nabil F.; Shin, Dong M.; Bruner, Deborah W.; Miller, Andrew H.
Abstract : BACKGROUND: Human papillomavirus (HPV) infection has contributed to an increased incidence of squamous cell carcinoma of the head and neck (SCCHN). Fatigue is a major side effect of SCCHN and its treatment. However, to the authors' knowledge, the association between HPV and fatigue has not been examined to date, nor is it known whether HPV influences biological mechanisms of fatigue, including inflammation. METHODS: Patients with SCCHN who were without distant metastasis were assessed at baseline (pre‐radiotherapy) and 1 month and 3 months postradiotherapy. Fatigue was measured using the Multidimensional Fatigue Inventory. Peripheral inflammation was assessed by plasma C‐reactive protein (CRP), interleukin 1 receptor antagonist (IL‐1ra), soluble tumor necrosis factor receptor 2 (sTNFR2), and IL‐6. Mixed effect models were used to examine associations. RESULTS: A total of 94 patients who were newly diagnosed were enrolled; 53% had HPV‐related tumors. Patients with HPV‐unrelated tumors had higher fatigue and higher plasma CRP, sTNFR2, and IL‐6 over time, especially at baseline and 3 months after intensity‐modulated radiotherapy compared with those with HPV‐related tumors (all P  < .05). However, fatigue and plasma sTNFR2 increased more significantly from baseline to 1 month after radiotherapy in the HPV‐related group compared with the HPV‐unrelated group (both P  < .01). Controlling for significant covariates, HPV status and inflammation were found to be independent predictors of fatigue over time. CONCLUSIONS: HPV status is an important marker of vulnerability to the behavioral and immune consequences of SCCHN and its treatment, providing support for different symptom management strategies. Special emphasis should be placed on addressing marked persistent fatigue in patients with HPV‐unrelated tumors, whereas attention should be paid to the large increases in fatigue during treatment among patients with HPV‐related tumors. Cancer 2018. © 2018 American Cancer Society . Abstract : Patients with human papillomavirus (HPV)‐unrelated head and neck cancers (HNCs) demonstrate higher fatigue and inflammation compared with those with HPV‐related HNCs at baseline and at 3 months after intensity‐modulated radiotherapy (IMRT). Nevertheless, patients with HPV‐related HNC experience a larger increase in fatigue and inflammation at 1 month post‐IMRT, whereas patients with HPV‐unrelated tumors experience persistently high levels of fatigue over time.